Exploring the Impact of Key Assembling Parameters on the Electrochemical Performance of Lithium Metal Symmetry Cell. Issue 2 (29th January 2020) - Wen, Zhipeng; Lin, Yinxin; Peng, Yueying; Zeng, Jing; Zhao, Jinbao
Abstract : With the urgent demand for higher energy density storage system, much attention has been focused on the Li metal based batteries. During the exploration of new strategy for the Li metal protection, numerous researches are based on Li/Li symmetry cell for galvanostatic cycling tests. Here, we systematically explored the relationship between some experimental parameters (size of Li foil, thickness of separator and electrolyte amount) and Li/Li symmetry cell cycling performance. And we find that the cycling stability of Li/Li symmetry cell has been significantly improved when the size of Li foil decreases or the thickness of separator increases. In the designed experiments, it can be seen that the failure of most of cells is attributed to the decrease in ions transport ability due to continuous consumption of the electrolyte and continuous increase of dead Li. At last, the investigation of electrolyte amounts reveals that Li/Li symmetry cell exhibits lower Li deposition overpotential and longer cycling life as adding more electrolytes. Therefore, our work suggests that research on the protection of electrolyte is very important issue in promoting the commercialization of Li metal batteries. And standardizing experimental parameters during the experiment can make more efficient comparison of different literature results achieved.